INTERNAL COMMUNICATION STRATEGY OF LEADERS WITHOUT A PUBLIC RELATIONS FUNCTION AT THE DOLOK ILIR TENERA MACHINE FACTORY - Dian Permatasari; Muhammad Husni Ritonga (Program Pascasarjana UIN Sumatera Utara, 2026)
This study aims to analyze the internal communication strategy of leaders at the Tenera Machine Factory (PMT) Dolok Ilir, a manufacturing organization operating without a formal Public Relations (PR) department. Using a descriptive qualitative approach with a case study, data were collected through in-depth interviews, observation, and documentation. The results show that the unit leader performs a substitution function for PR through a hybrid communication strategy. This strategy integrates the use of WhatsApp Groups as a digital channel for rapid and transparent information dissemination, combined with interpersonal communication through